THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER, AND RETURN ON ASSET ON INCOME GROWTH IN COAL SUBSECTOR COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE FOR THE PERIOD 2016-2018 - Juliana Juliana; Kasmawati Kasmawati; Irfan Tanjung (STIE Bangkinang Publishing, 2020)
The purpose of this study was to determine and analyze the effect of Current Ratio, Debt To Equity, Total Asset Turnover, and Return On Asset on profit growth in coal sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2018. Sampling was done by purposive sampling method of 10 companies. The data analysis technique was carried out with multiple linear regression models. Based on the test results simultaneously and partially, all variables proved to have a significant effect on profit growth. The closeness of the relationship between variables is strong with the correlation coefficient (R) obtained at 71%. Meanwhile, the independent variable contribution to the dependent variable is 43%. Meanwhile, 57% is explained by other variables that are not included in this research model.